PENGARUH KEPEMILIKAN KELUARGA, FINANCIAL DISTRESS DAN THIN CAPITALIZATION TERHADAP PENGHINDARAN PAJAK - Safitri, Selistiaweni (2020)
This research is a quantitative study that aims to determin the effect of fammily ownership, financial distress, and thin capitalization on tax avoidance. The study was conducted using manufacturing companies that have been listed on the Stock Echange in 2015-2018. The selection of manufacturing companies in this study uses a purposive sampling method and the number of acceptable sample is 292 of the total. Hypothesis testing in the study used panel data regression analysis with the STATA 13 program and a significance eve of 5% (0.05). The resultyof the test a obtained (1) there is no significan effect on familly ownership of tax avoidance, (2) there is significant negative effect on financial distress of tax avoidance, (3) ther is no significan effect on thin capitalization of tax avoidance.